Periodos de precalentamiento en huevos fértiles Cobb 500 en parámetros de incubación al nacimiento - Mendoza Meneses, Jenny Elizabeth (2021)
The objective of the research was to evaluate the warm-up periods in fertile cobb 500 eggs in incubation parameters at birth. A DCA was applied with a 2x3 factorial arrangement, having as factors under study the following: Factor A Temperature of 25 and 30 ° C and Factor B Preheating periods of 8, 12 and 16 hours. The variables to be measured were: (infertility, fertility, contaminated eggs), embryonic mortality during incubation (MET, MEI, META), weight loss of eggs during incubation, chick productivity (first, second and discard chickens) and chick weight in relation to egg weight, evaluated in percentage. The results obtained were regarding the percentages of embryonic mortality: MET 61.52% for T5 and 37.25% for T3; MEI 10.29% for T6 and 5.39% for T2; GOAL 5.14% for T3 and 1.71% for T5. Regarding the productivity of the first, second and discard chicks, the highest results were 4.65% for T6 and 1.22% for T4. The ideal temperature and warm-up period for the incubation process are 25 ° C and 16 hours. The weight loss of the eggs during incubation was 16.92% for the T5 and the yield of the chick weight in relation to the egg weight was 74.06% for the T5. It is concluded that preheating is an important factor that intervenes in the hatchability and quality parameters of the BB chick.